RELATIONSHIP BETWEEN CONDICTIO AND VERSIO CLAIMS IN MODERN LAW - Stefanović, Aleksandra (Glasnik Advokatske komore Vojvodine, 2022)
Author analyses claim for the unjust enrichment throughout two institutes: condictio and actio de in rem verso. Both of them originate from roman law, though their essence has been drastically changed in the modern laws. As a previous step, it is necessary to put them in a relationship with other lawsuits so they can be negatively defined in order to determine their boundaries. In order to make an adequate comparison, their similarities and differences should be taken into account as well as different conceptions of this lawsuit that occur in foreign legal systems. Comparative and dogmatic methods are used in the article.
Keywords: Condictio. – Version. – Relationship. – Claim. – Obsolescence.